The Quality of Newly Local Content Based Instructional Reading Materials for Senior High School Students - Shella Monica; Rambat Nur Sasongko; Muhammad Kristiawan (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aimed to analyze the quality of advanced local content-based instructional reading material. It was ten descriptive texts and a reading comprehension test with the topic focused on Bangka Island tourism places. The developed product was specially constructed by considering the reading level of senior high school students in Pangkalpinang, Indonesia, which is identified at level four. The quality of the product reflects on its effectiveness and criterion-related validity. The point is determined from students' scores on the reading comprehension test administered after they have been taught using the developed product in 6 meeting sessions. The criterion-related validity of developed reading comprehension was recognized by measuring the correlation between students' scores on progressive reading comprehension tests and their scores on standardized reading level tests. Based on the result, the developed product can be considered adequate because 35 students (85.36%) out of 41 students in reading comprehension test accomplished the minimum mastery criterion, which was 70. The product was also considered good in terms of its criterion-related validity because the correlation coefficient was 0.618. Since findings show that the developed local content-based instructional reading materials are effective and valid, it can conclude that the developed product has good quality when used as instructional reading materials for senior high school students. Keywords: Instructional Reading Materials, Local Content, Senior High School Students